The Iberians in Cerdanya: archaeology and epigraphy (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
The language of the more than 180 rock inscriptions in Iberian script in Cerdanya is Iberian, confirming the Ibericity of the Ceretans, which had once been questioned according to their archaeological culture. In Cerdanya, two large epigraphic schools can be identified, the dual and the non-dual, the dual being slightly the majority, which would correspond to the oldest, probably from the s. 3rd c. BC or earlier, while the non-dual should be the most modern. This epigraphic chronology would fit with the two phases of the Iberian settlement in Cerdanya that derives from the latest archaeological excavations, the Ceretan phase, from the beginning of the s. 4th c. BC until the middle of the s. 2nd c. BC and the Ceretano-Republican phase from this chronology to the third quarter of the s. 1st c.  BC.
Keywords: Iberians; Ceretans; Iberian inscriptions; Iberian language; rock inscriptions